Effects of video-based exercises and conventional physiotherapy on upper extremity functionality, selective motor control, and proprioception in unilateral cerebral palsy: A randomized controlled trial - Karabulut, Demet Gözaçan; Maden, Çağtay; Karabulut, Yalçın; Aslan, Mehmet (Mary Ann Liebert Inc., 2024)
Objective: The present study was conducted to evaluate the effects of video-based exercises added to conventional physiotherapy (CPT) on upper extremity functionality, selective motor control, and proprioception in individuals with unilateral cerebral palsy (UCP). Materials and Methods: Thirty patients with UCP were randomized into two groups: the intervention group (15 individuals with a mean age of 9.2 – 3.8 years) and the control group (15 individuals with a mean age of 8.3 – 4.1 years). The intervention group received 8 weeks of video-based exercises, and the control group received 8 weeks of conventional physiotherapy. Upper extremity functional abilities, upper extremity selective motor control, proprioception, and entertainment levels were evaluated before and after the intervention for all groups. Results: While a significant change was observed in the mean scores of the ABILHAND-Kids, Selective Control of the Upper Extremity Scale right-left scores, shoulder flexion, shoulder abduction, and elbow flexion proprioception angles after the video-based exercises in the intervention group (P < 0.05), a significant change was observed only in the 60-degree flexion angle in the control group (P = 0.001). In the comparison between the groups, there were significant differences in post-intervention value only in shoulder flexion and abduction angles, whereas there was no difference between the groups in elbow flexion angles (P > 0.05). Conclusion: Incorporating video-based exercises into the upper extremity rehabilitation processes of individuals with UCP is beneficial in terms of upper extremity functionality, selective motor control, and proprioception. © Mary Ann Liebert, Inc.
Keywords: active video gaming; cerebral palsy; proprioception; selective motor control; upper extremity; virtual reality